Effect of management (organic vs conventional) on volatile profiles of six plum cultivars (Prunus salicina Lindl.). A chemometric approach for varietal classification and determination of potential markers. (15th May 2016) - Cuevas, F.J.; Moreno-Rojas, J.M.; Arroyo, F.; Daza, A.; Ruiz-Moreno, M.J.
Highlights: Hexanal was the main volatile in plums and was affected by the cultivation system. Five volatiles were described for the first time in Prunus salicina Lindl. The aroma profile allowed us to discriminate among cultivars using chemometrics. The chemometric approach let us identify volatile markers for cultivars. Abstract: The volatile profiles of six plum cultivars ('Laetitia', 'Primetime', 'Sapphire', 'Showtime', 'Songold' and 'Souvenir') produced under two management systems (conventional and organic) and harvested in two consecutive years were obtained by HS–SPME–GC–MS. Twenty-five metabolites were determined, five of which (pentanal, ( E )-2-heptenal, 1-octanol, eucalyptol and 2-pentylfuran) are reported for the first time in Prunus salicina Lindl. Hexanal stood out as a major volatile compound affected by the management system. In addition, partial least square discriminant analysis (PLS-DA) achieved an effective classification of genotypes based on their volatile profiles. A high classification accuracy model was obtained with a sensitivity of 97.9% and a specificity of 99.6%. Furthermore, the application of a dual criterion, based on a method of variable selection, VIP (variable importance in projection) and the results of a univariate analysis (ANOVA), allowed the identification of potential volatile markers in 'Primetime', 'Showtime' and 'Souvenir' genotypes (cultivars not characterised to date).